Film editing and the factors that shape it - Maschler, Nathan; Truhlář, Filip; Michalik, Pavel, 1972-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This thesis goes into detail about the creative and technical functions of editing in film. It covers everything that should be going through an editor’s mind when they are deciding when to cut from one shot to the next, and how to best transition between them. This text primarily focuses on editing for narrative-driven films, however, much of the information presented is applicable to any type of video editing.
Vedoucí práce: Filip Truhlář
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses